Validation study of the portuguese version of the QLC-C30-V.3 - Pais-Ribeiro,J. (2008)
The purpose of this research was to study the metric properties of the Portuguese translation of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core-30 (EORTC QLQ-C30, version 3). A heterogeneous cancer patient sample of 933 subjects, 61.5% female, mean age 54.24 years, mean school age years of 6.9 years, with a diagnosis from one month to 31 years, was used. The questionnaire seems to be sensitive to cancer sites but not to the number of years with the disease. Mean values for the scales, and reliability are appropriate and show similar patterns to other versions from different cultures and languages. Correlations between scales show moderate correlations suggesting that they measure different and complementary constructs, which constitute important information for clinicians in the followup of this population. We can say that the Portuguese version of the QLQ-C30 has good metric properties, and measures the same constructs, the same way, as the versions from other languages and cultures, and it is appropriate to be applied to people with cancer disease